Corneal stromal mapping characteristics in normal corneas using anterior segment SD-OCT - Abusamak, Mohammad; Issa, Sara Mazen; Alomari, Amal F.; Alsalamat, Husam A.; Haj Ali, Nour S.; Izmegna, Abdallah; Shawashreh, Mais; Abu Samak, Mahmoud; Abusamak, Talal M. (Frontiers in Medicine, 2024)
This study investigated how normal corneal stromal profiles change with age, sex, and corrected intraocular pressure (IOP).A retrospective observational analytical study was conducted in Jordan, employing anterior segment spectral-domain optical coherence tomography AS-OCT, a measured corneal stromal thickness (CST) in 134 eyes across the central 6-mm corneal diameter. People between the ages of 18 and 79 were included, and the mean CST values were linked to age groups, IOP, and cis-gender populations, with the exclusion of certain eye conditions. The central stroma was thinnest at 484.6 (±32.6) µm, contrasting with the outer peripheral superior zone's maximum thickness at 549.3 (±40.6) µm. A positive correlation between CST and the 30-49 age group was noted. In conclusion: this study highlights a centrifugal CST distribution, with the central stroma being the thinnest and the superior stroma being the thickest. AS SD-OCT, employing novel algorithms, proves vital in refractive surgery planning and corneal disease diagnosis. The research offers valuable insights into age, gender, and IOP interactions with corneal stromal characteristics, enhancing clinical strategies for corneal pathologies in the Jordanian population.